A Correction Method of Estimating the Pointing Error for Reflector Antenna - Jie Zhang; Jin Huang; Wei Liang; Youran Zhang; Qian Xu; Letian Yi; Congsi Wang (Shock and Vibration)
The pointing error caused by the structural deformation of large reflector antennas has become the most challenging problem of antenna servo control. Especially with the increase of the antenna diameter and the working frequency, environmental loads not only make the structure deformation more obvious, but also make the pointing accuracy influenced by deformation more sensitive. In order to solve this problem, accurately estimating the pointing error caused by the structural deformation is the key. Based on the dynamic model of antenna structure and the analyzing model of pointing error, using the displacement information of sampling points on reflector, this paper proposes a correction method to achieve the purpose of accurately estimating the pointing error caused by the structural deformation. Using a 7.3-m Ka band antenna, the results show that the antenna maximum pointing error in theoretical model calculation is 0.0041° at 10m/s wind speed condition; however, the corrected pointing error would be about 0.0054° with considering the modeling error. After compensating the controller, the pointing error could be reduced to only 0.0008° and the performance of antenna pointing was improved.